Optimalisasi Waktu Produksi, Jumlah Produksi, Dan Jalur Distribusi Pada Oulet Lazatto di Karawang - Lestari, Cici; Sari, Rianita Puspa (Jurnal Sistem Teknik Industri, 2021)
The development of the food and beverage business is still recorded as a number of high developments in this world, the types of food and beverage in various forms have increased because food is one of the basic needs that must be met. Lazatto is a food industry that is engaged in various fields of fast food restaurants by producing processed chicken. The problems that occur at Lazatto are the inability to maximize the amount of chicken production, optimize the production time for employees, and the distribution channel to determine the shortest route to utilize raw materials. The purpose of this research is to analyze the optimization of working time using the Hungarian method or assignment, the amount of production using the Branch and Bound method, and the distribution line using the Minimum Spanning Tree method. The results showed that the optimal working time is 83 minutes or 1 hour 23 minutes / one time production, the amount of production in one production is 23 pieces with a combination of 5 pieces of geprek chicken, 4 pieces of sadas chicken, and 14 pieces of fried chicken, with The optimal total distance for the distribution of raw materials is 137.6 km.